2019
DOI: 10.1371/journal.pone.0225972
|View full text |Cite
|
Sign up to set email alerts
|

Walking with head-mounted virtual and augmented reality devices: Effects on position control and gait biomechanics

Abstract: What was once a science fiction fantasy, virtual reality (VR) technology has evolved and come a long way. Together with augmented reality (AR) technology, these simulations of an alternative environment have been incorporated into rehabilitation treatments. The introduction of head-mounted displays has made VR/AR devices more intuitive and compact, and no longer limited to upper-limb rehabilitation. However, there is still limited evidence supporting the use of VR and AR technology during locomotion, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…Our findings supported the notion that cadence and stride length might not be a determining factor in impact mechanics, as suggested by previous studies. 12,31 These studies reported similar stride length and cadence among RFS and non-RFS runners, and demonstrated either no or weak relationship between cadence and vertical loading rate.…”
Section: Discussionmentioning
confidence: 85%
“…Our findings supported the notion that cadence and stride length might not be a determining factor in impact mechanics, as suggested by previous studies. 12,31 These studies reported similar stride length and cadence among RFS and non-RFS runners, and demonstrated either no or weak relationship between cadence and vertical loading rate.…”
Section: Discussionmentioning
confidence: 85%
“…The risk of this technology is the impossibility to recognize real dangers that can cause injuries. In AR, virtual reality and real reality overlap and the patient is aware of potential dangers [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was feasible and useful to use AR with older adults in the community to evaluate different design features for the redesign of a public park to encourage an active lifestyle among older adults. Chan et al [ 39 ] evaluated spatiotemporal gait parameters of treadmill walking in three conditions: (1) control, (2) AR, and (3) VR, and found a significant difference in stride length and cadence between the control and AR conditions. In contrast, we found neither wearing AR glasses nor the display of different design features significantly affected the participants' gait on a park pathway.…”
Section: Discussionmentioning
confidence: 99%